Pengaruh FDI, Labour Productivity dan Teknologi Terhadap Pertumbuhan Ekonomi European Union - Ulya Khasanah; Dedy Yuliawan (CV. Multi Kreasi Media, 2023)
The purpose of this study is to describe the effect of foreign direct investment or FDI, labor productivity and technology proxied by patent application data on economic growth in the 18 European Union countries that are members of the OECD. The scientific technique used in this study is a panel data analysis strategy with the selection of Fixed Effect Models in 18 European Union countries, namely Austria, Belgium, Czech Republic, Denmark, Estonia, Finland, France, Hungary and Ireland. , Italy, Latvia. , Netherlands, Poland, Portugal, Slovakia, Slovenia, Spain and Sweden for the 2014-2019 period. The dependent variable in this study is economic growth, while the independent variable is FDI, labor productivity and technology with patent application data. The results of this study indicate that FDI and labor productivity have a positive and significant effect on economic growth. Meanwhile, technology with patent application data has a positive and insignificant impact on economic growth.